Identifying optimal locations for mobile first aid facilities in Bucharest, accounting for seismic risk (GeoPatterns, 2024)
In case of a major earthquake in the Vrancea area, Bucharest can be significantly affected (as it happened in 1940 and 1977). As highlighted by these events, the need for establishing mobile first aid facilities close to affected areas (deployment of medical containers or mobile hospitals) is expected to be of high importance for saving lives. In this research we identify the need of suchfacilities and the favorable locations, considering multiple earthquake scenarios. Our methodology is based on multicriteria analysis in which we use the SMCE module of the ILWIS geospatial program and take into account three indicators: (i) the estimated losses in terms of affected residential buildings and occupants, calculated for 3 earthquake scenarios, (ii) distances from buildings with highseismic risk levels (categories I and II) and from important traffic routes, and (iii) road network connectivity loss after a major earthquake. The results identified the central and peripheral area as having complex issues and the need for future analyzes at the neighborhood level.